2021
DOI: 10.1101/2021.01.10.426061
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Occurrences of protonated base triples in RNA are determined by their cooperative binding energies and specific functional requirements

Abstract: With wide ranging diversity in their geometries, binding strengths and chemical properties, noncanonical base pairs are equipped to intricately regulate and control the structural dynamics of RNA molecules. Protonation of nucleobases adds to the diversity. Compared to the unprotonated scenario, on one hand they open up new alternatives for base pairing interactions (Class I) while on the other, they modulate the geometry and stability of existing base pairing interactions (Class II). In both cases, compensatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 117 publications
0
1
0
Order By: Relevance
“…57,58 We chose oB97X-D, since it is an improved, range-separated version of the Becke's original 97 functional 59 that includes both long range correction to the non-Coulomb part of exchange functional and second order dispersion correction, and has been used in a previous similar study on biologically-relevant hydrogen-bonded complexes. 60 Furthermore, a benchmarking of the performance of DFT functionals for studying the optimized geometry, stability and cooperativity of DNA triplexes has shown that the results of the parent B97-D functional are consistent with higher theoretical levels. 61 The dispersion correction within the oB97X-D was implemented using the Grimme's 'DFT-D2' model, 62 albeit with a different damping function and unscaled dispersion correction to model the correct asymptotic pairwise vdW potentials.…”
Section: Qm Calculationsmentioning
confidence: 82%
“…57,58 We chose oB97X-D, since it is an improved, range-separated version of the Becke's original 97 functional 59 that includes both long range correction to the non-Coulomb part of exchange functional and second order dispersion correction, and has been used in a previous similar study on biologically-relevant hydrogen-bonded complexes. 60 Furthermore, a benchmarking of the performance of DFT functionals for studying the optimized geometry, stability and cooperativity of DNA triplexes has shown that the results of the parent B97-D functional are consistent with higher theoretical levels. 61 The dispersion correction within the oB97X-D was implemented using the Grimme's 'DFT-D2' model, 62 albeit with a different damping function and unscaled dispersion correction to model the correct asymptotic pairwise vdW potentials.…”
Section: Qm Calculationsmentioning
confidence: 82%